Beyond Metros: Strategies for Penetrating the Tier-2 Luxury Market in India - Maloloy-on, Deenah Joy; Villa, April Rose; Pelmin, Monsour; Botes, Jenly; Esquera, Jackie (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2025)
This study uses specific tactics to examine how luxury brands may effectively enter tier-2 cities in India. These cities are becoming important development locations for the luxury sector as digital technology, urbanization, and increasing disposable income change customer behavior. The study intends to find efficient marketing plans catered to this changing customer base. The article evaluates important trends and issues of luxury companies entering tier-2 markets using secondary data, including industry reports, market surveys, and case studies. Its market entry and engagement conceptual framework is based on insights from real-world brand experiences and top consultancy companies. Results show that individualized consumer experiences, localized branding, and digital-first policies are absolutely vital. Important marketing methods include social media interaction, partnerships with local influencers, pop-up stores, and special local events. Maintaining a balance between the worldwide reputation of luxury brands and the cultural sensitivities of tier-2 consumers will define success. This study offers unique value by changing the emphasis from conventional urban markets to the untapped potential of India's tier-2 cities. It offers practical ideas for luxury firms looking to grow into these areas and those with more specific demands and tastes.